Monitoring status of public procurement by IMED and compliance issues of PPA-2006 and PPR-2008 - Rahman, Md. Mumitur (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.